Activities of the summer party of the 24th Japanese Antarctic Research Expedition in 1982-1983 - Yoshikuni Ohyama (National Institute of Polar Research, 1984)
This report outlines the summer activities of the 24th Japanese Antarctic Research Expedition (JARE-24) in 1982-1983. The expedition consisted of 35 wintering members led by Dr. Shinji MAE and 10 members of the summer party led by the present author. Three American exchange scientists under the Antarctic Treaty provisions joined the summer party from Tokyo to Fremantle (Dr. T. GOSINK and Mr. T. GREEN) and from Fremantle to Singapore (Mr. G. LANDRETH). The icebreaker FUJI left Tokyo on November 25,1982. After calling at Fremantle, she arrived at the ice edge off Syowa Station on December 31,when the first flight to the station was made. All the cargo for the expedition was transported to the station till January 22,1983 and the wintering members of the JARE-24 took over the duties at the station on February 1. After accomplishment of summer operations in the Syowa Station area, FUJI visited Breid Bay about 600km west of the station. Then she returned to Tokyo on April 20,1983 via Port Louis and Singapore. Oceanographic and ionospheric observations were carried out throughout the voyage. Several field parties for geological, biological and geodetic survey were sent to ice-free areas around Syowa Station. Biological and oceanographical observations under sea ice were carried out at Syowa Station. A party was dispatched to Mizuho Station to take over it and to resupply the materials for wintering. A new power station building at Syowa Station was constructed during the relief period. In the Breid Bay area, the condition of sea ice was observed and some glaciological surveys were carried out in the snow field 30 miles from the ice shelf edge. Also aerial reconnaissance was carried out to find the access route to the Sor Rondane Mountains.